ESTETIKA BAHASA PETUAH ADAT MASYARAKAT TAPUNG - Tamtowi Yahya; Elmustian Elmustian; Hermandra Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study describes an aesthetic language that is present on the Tip of the indigenous Community Tapung. The purpose of this research is to identify and describe the elements of an aesthetic language that is present on the Tip of the indigenous Community Tapung. This research uses qualitative rather than quantitative research types or numbers. Data collection techniques in the study using interview techniques and record. Data acquired as much as custom tip 46 tip custom. The aesthetic elements of the language are examined in the Tip of the indigenous Community Tapung consists of diction and imagery. Based on the results of the research, from all 46 tip custom obtained and containing elements of aesthetic diction or imagery. As for the data include, diction were analyzed based on words and phrases 18 numbered numbered 8 out of 12 tip, imagery vision as much as 17 tips from 46 tip, imagery hearing 7 tip from 46 tip, tip 15 motion imagery of 46 tip, imagery smell 2 tip from 46 tip, imagery taster 4 tip from 46 tip, imagery feelings 6 tip from 46 tip.Key Words: The Aesthetic Language, Diction, Citraan, Tip Of The Indigenous Community Tapung.